Disorder‐Driven Collapse of Topological Phases in Photonic Topological Insulator. Issue 10 (31st May 2022) - Zhang, Hongfang; Sui, Wenjie; Zhang, Yu; Liu, Gangcheng; Shi, Qiang; Lv, Zengtao; Zhang, Dong; Rong, Chuicai; Yang, Bing
Abstract : By embedding the position disorder of rods in 2D gyromagnetic photonic crystal, the influences of increasing random disorder on the photonic topological phases (PTPs) in a photonic topological insulator are numerically investigated. When the disorder is small, the PTPs almost have no change. With the increase in disorder, the PTPs at the edge of the original topological bandgap are first affected, and those at center of the bandgap have the best robustness. As disorder increases to a critical value, the PTPs collapse ultimately. During the collapse of the PTPs, disorders can induce the Anderson localization of electromagnetic (EM) wave, and produce localized hot spots in the system. When the disorder is not too large, the hot spots are excited at the edge area near the excitation source, and have little influence on the one‐way propagation of the topological edge state (TES). As disorder increases continuously, the hot spots would penetrate the system deeply and affect the propagation of EM waves significantly, which leads to the collapse of the PTPs and destruction of one‐way propagation of TES. Even so, there are still remaining long‐range and short‐range orders in the system. This research provides a theoretical model and an experiment platform for further studying the relationship between topological phases and disorders. Abstract : Increasing random disorders in photonic topological insulators collapse the photonic topological phases (PTPs) gradually. During the collapse of the PTPs, the disorder can induce competition between Anderson localization and one‐way propagation of topological edge states, and produce localized hot spots in the system. Even after the PTPs are collapsed, there are still remaining long‐range and short‐range orders in the system.